Utilization of Eco-Enzymes from Fruit Skin Waste as Hand Sanitizer - Rusdianasari Rusdianasari; Adi Syakdani; Muhammad Zaman; Febby Fitria Sari; Nabila Putri Nasyta; Rizka Amalia (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2021)
Eco-enzyme is a multifunctional liquid produced from fermentation of waste or organic waste, brown sugar or granulated sugar, and water. Fermentation of eco-enzymes is carried out for ±3 months. The length of time fermentation affects color, aroma and pH. The resultingeco-enzyme liquid is dark brown and has a strong fresh sour aroma. Eco-enzymeliquid has an alcohol content and acetic acid. Alcohol and acetic acid are produced from the bacterial metabolic process that is naturally present in the rest of fruits and vegetables. Variations in the fermentation time of eco-enzymes used are 2.5 months and 3 months. Analysis conducted on eco-enzymes include pH tests and phytochemical screening tests. The pH value obtained in eco-eznyme 2.5 months is 3, while the pH value in eco-eznyme 3 months is 1.5. Eco-enzymes with a fermentation time of 3 months contain alkaloid compounds, flavonoids, saponins, and tannins. In this study Eco-eznyme was used as a hand sanitizer spray by diluting the eco-enzyme with aquadest. The dilution ratios used vary for each sample: 1:40, 2:40, 3:40, 4:40, 5:40. Analysis conducted on hand sanitizer spray include pH test, organoleptic test, and antibacterial activity test. Based on the results of the analysis, not all hand sanitizer samples meet SNI standards, the best samples obtained in hand sanitizer with an eco-enzyme fermentation time of 3 months and a dilution ratio of 5: 40. The results of the analysis showed that the value of pH 5, the level of aroma fondness in hand sanitizer 2.40, the favorite color level 2.46